Knowledge, Attitude, and Practices towards COVID-19 during the Rapid Rise Period: A Cross-Sectional Survey among Public University Students of Bangladesh - Md Mostafizur Rahman; Jannate Mehjabin Jhinuk; Nadia Habib Nabila; Mir Taj Mira Yeasmin; Ifta Alam Shobuj; Tammim Hossain Sayma; Fariha Faruk; Shakhawat Hossain Shah (Ital Publication, 2021)
Bangladesh has experienced long term COVID-19 impact in the education sector where university students have suffered a lot. This cross-sectional study intended to evaluate the health behavior of public university students towards the COVID-19. The convenience sampling technique was employed during the rapid COVID-19 period. A total of 952 public university students participated in the KAP survey. Statistical analyses were performed depending on the data type. Study population demonstrated exemplary COVID-19 knowledge along with positive attitudes and preventive practices towards the COVID-19. Gender, university year, and major were determined as associating factors with their overall KAP. Female students reported better knowledge and practice regarding COVID-19 than their counterpart male students. Students living in the capital Dhaka city did not show positive attitudes towards COVID-19 compared to the students living outside the city. Students who were without their families demonstrated better attitudes compared to the students with their families. Broadcast media, print media, the internet, university, and social media were identified as sources of COVID-19 precautionary measures information for these students. Students showed better knowledge and attitude levels when used print media and university respectively compared to the students who used surrounding people as a source of information. This study enhances our understanding of the health behavior of public university students of Bangladesh. It has also determined the associating factors with their KAP level. The outcome of this study can assist the government, organizations, and the university to prepare for a comprehensive pandemic control effort.   Doi: 10.28991/SciMedJ-2021-0302-4 Full Text: PDF